Cooperation between emotional players - Lina Andersson (Games, 2020)
This paper uses the framework of stochastic games to propose a model of emotions in repeated interactions. An emotional player can be in either a friendly, a neutral, or a hostile state of mind. The player transitions between the states of mind as a response to observed actions taken by the other player. The state of mind determines the player's psychological payoff which together with a material payoff constitutes the player's utility. In the friendly (hostile) state of mind the player has a positive (negative) concern for other players' material payoffs. This paper shows how emotions can both facilitate and obstruct cooperation in a repeated prisoners' dilemma game. In finitely repeated games a player who cares only for their own material payoffs can have an incentive to manipulate an emotional player into the friendly state of mind. In infinitely repeated games with two emotional players less patience is required to sustain cooperation. However, emotions can also obstruct cooperation if they make the players unwilling to punish each other, or if the players become hostile when punished.
Keywords: C73; D01; D91; 330; cooperation; emotions; repeated prisoners' dilemma; stochastic games